Effectiveness of Recruitment of Honorary Staff at the Civil Service Police Unit and Wilayatul Hisbah, Gayo Lues Regency, Aceh Province - Hendra Hendra*; Muhammad Bin Abu Bakar; Florentina Ratih Wulandari (Riwayat: Educational Journal of History and Humanities, 2024)
The effectiveness of recruitment of honorary workers at the Civil Service Police Unit can improve the service performance of the Wilayatul Hisbah of Gayo Lues Regency. The purpose of writing this scientific paper is to analyze and recommend how to implement the recruitment of Honorary Workers at the Civil Service Police Unit and Wilayatul Hisbah of Gayo Lues Regency, Aceh Province. Subjects of the study The data sources in this study were the Assistant for Government and Social Welfare of Gayo Lues Regency, Head of Civil Service Police Unit and WH of Gayo Lues Regency, Head of BKPSDM Gayo Lues, Head of Public Order and Public Security Division of Civil Service Police Unit and WH Gayo Lues, Head of Human Resources Division of Apparatus and Community Protection Unit, Head of General and Personnel Sub-Division of Civil Service Police Unit and WH Gayo Lues and Head of Human Resources Section. The data collection technique for this study was conducting in-depth interviews in general, which is a process of obtaining information in research objectives and observation is part of one of the data collection techniques for qualitative research, where comprehensive researcher insight is needed to find field phenomena and symptoms that may occur in a study. The results of the study are: the effectiveness of recruitment of honorary personnel in the Civil Service Police Unit and Wilayatul Hisbah of Gayo Lues Regency is studied considering the priority of its main tasks and functions as enforcers of regional regulations or district qanuns, regional regulations (perda), especially in the field of public order, security and protection of the community which is the authority of the region so that it requires the apparatus of the Civil Service Police Unit and WH Gayo Lues to have a reliable and quality attitude and management. Carrying out matters of public order, security, protection of the community, the field of policy enforcement carrying out coordination, administrative and technical services for the preparation of planning, management, legislation, correspondence and archiving, public relations, households, performance reports, documentation, finance and assets, reporting and evaluation and affairs of the State Civil Apparatus within the Region, Islamic Law, Human Resources and Community Protection.